LncRNA00492 is required for marginal zone B‐cell development. Issue 1 (7th September 2021) - Wang, Faming; Cui, Dongya; Zhang, Qingyun; Shao, Yingying; Zheng, Baijiao; Chen, Liling; Luo, Yao; Yuan, Liudi; Wang, Demin
Abstract: B‐cell development undergoes a series of steps from the bone marrow to the secondary lymphoid organs. A defect in B‐cell development can lead to immunodeficiency or malignant disorders, such as leukaemia or lymphoma. Long non‐coding RNAs have been reported to act as important regulators of many pathological processes. However, very little is known regarding the role of lncRNAs during B‐cell development and the regulation of their expression. In this study, we explored the expression and role of lncRNA Gme00492 in B‐cell development. We observed that lnc00492 was highly expressed in B‐cell development and primarily expressed in the nucleus. Lnc00492‐deficient mice had fewer marginal zone B cells in the spleen, likely due to a developmental block. Importantly, lnc00492 interacts with CTBP1 and targets it for ubiquitination and degradation during B‐cell development, whereas the transcriptional corepressor factor CTBP1 plays a critical role in Notch2 signalling. Thus, we identified a novel regulatory axis between lnc00492 and CTBP1 in B cells, suggesting that lnc00492 is essential for marginal zone B‐cell development. Abstract : Lnc00492 interacts with transcriptional corepressor factor CTBP1 to activate its ubiquitinated proteasome degradation pathway and promote the degradation. The decrease of CTBP1 enhances the transcription of Hes1/5. High expression of Hes1/5 activates the Notch2 signaling pathway and promotes the development of MZ B cells.